Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1371/journal.ppat.1004319
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Dictation of Japanese Encephalitis Virus-Induced Neuroinflammation and Lethality via Triggering TLR3 and TLR4 Signal Pathways

Abstract: Japanese encephalitis (JE) is major emerging neurologic disease caused by JE virus. To date, the impact of TLR molecules on JE progression has not been addressed. Here, we determined whether each TLR modulates JE, using several TLR-deficient mouse strains (TLR2, TLR3, TLR4, TLR7, TLR9). Surprisingly, among the tested TLR-deficient mice there were contrasting results in TLR3−/− and TLR4−/− mice, i.e. TLR3−/− mice were highly susceptible to JE, whereas TLR4−/− mice showed enhanced resistance to JE. TLR3 ablation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 60 publications
4
99
0
Order By: Relevance
“…While circulation of cytokines and chemokines is known to facilitate BBB breaking and viral neuroinvasion (48,(52)(53)(54), we found that proinflammatory cytokines or immune response-related genes were induced only once the virus could be detected in the mouse brain (Fig. 6).…”
Section: Discussionmentioning
confidence: 88%
“…While circulation of cytokines and chemokines is known to facilitate BBB breaking and viral neuroinvasion (48,(52)(53)(54), we found that proinflammatory cytokines or immune response-related genes were induced only once the virus could be detected in the mouse brain (Fig. 6).…”
Section: Discussionmentioning
confidence: 88%
“…Likewise, lack of TLR3 in mice infected with JEV was associated with higher frequency of inflammatory monocytes in the CNS, enhanced number of activated microglia, and elevated levels of IL-6 and TNF-α in the CNS, along with increased BBB permeability [212]. However, ablation of TLR3 did not alter virus titers in the CNS after intracranial inoculation of mice with JEV [212]. Conversely, in another study there was no significant difference in survival between wild-type and TLR3-deficient mice after intracranial infection with WNV [117].…”
Section: Innate Immune Response To Arboviruses In the Cnsmentioning
confidence: 93%
“…TLR3-deficient mice displayed increased viral load in the brain following intracranial challenge with WNV [116]. Likewise, lack of TLR3 in mice infected with JEV was associated with higher frequency of inflammatory monocytes in the CNS, enhanced number of activated microglia, and elevated levels of IL-6 and TNF-α in the CNS, along with increased BBB permeability [212]. However, ablation of TLR3 did not alter virus titers in the CNS after intracranial inoculation of mice with JEV [212].…”
Section: Innate Immune Response To Arboviruses In the Cnsmentioning
confidence: 94%
“…To support this hypothesis, recent experimental study done on mice with JE showed that JEV triggered inflammatory response through TLR3 and there was an increase in viral proliferation and reduced inflammatory response in TLR3 knockout mice. Reduced inflammatory response promotes viral proliferation (Lindenbach et al, 2007;Jiang et al, 2014;Han et al, 2014). It has been demonstrated that out of 136 single nucleotide polymorphisms (SNPs) described within the human TLR3 gene, only two SNPs [A851T (rs5743316), C1234T (rs3775291)] actually affect the TLR3 function.…”
Section: Introductionmentioning
confidence: 99%